The primary teacher education curriculum: implications for the restoration of the culture of teaching and learning in Kwa-Thema primary schools. - Netshifulani, Maite Maria (My University, 2014)
The capacity of South Africa’s teachers and lecturers is limited not withstanding the fact that they need to serve as primary agents of change in the classroom. The quality of the lecturers as well as the teacher education curriculum also leave much to be desired. The focus of this study is the effectiveness of prim aiy teacher education curriculum. Special attention is given to its responsiveness to the conditions which students encounter in Prim aiy Schools. Qualitative research methods were used in data gathering from two Colleges of Education in the East Rand and four Piimary Schools in Kwa-Thema, Springs. The report concludes that the teacher education curriculum is poorly matched to the skills trainees need to cope with unsatisfactory conditions at Primaiy Schools. The partnership between Colleges of Education and Primary Schools needs to be strengthened to forge a tighter relationship between teaching practice and theory.